Multiculturalism - Watson, C.W. (New Delhi : Viva Books, 2005)
Multicultural" and "multiculturalism" are words frequently used to describe the ethnic diversity that exists everywhere in the world today. However, there is some confusion about what precisely they signify. Do they simply describe diversity or are they advocating a particular response to that diversity? This book looks at some of the debates associated with these words and with the concepts attached to them. In
Includes reference and index
Keywords: Multiculturalism; Multikulturelle Gesellschaft; Multikulturelle Gesellschaft